Entre cozinhas e quitandas: patrimônio e globalização em Pirenópolis - Toralles, Katia Karam (2017)
This piece of writing/essay exposes the way of living and working of the quitandeiras in Pirenópolis, revealing how they represent the changes the city has gone through in the last 20 years, being driven by its development and by the increase of tourism. It starts from the recognization of the quitandas in the urban context and finds its way through the domestic universe to learn the meanders of this producing process, and to unveal the stories of the women who produce it. The activity produced by the quitandeira is seen as a part of the nutrional models which are exposed to the daily flows of information and people. Women take parte of this process/movement as agents of a social recomposition, giving a meaning to food and to the act of eating. The production of quitandas is a vector of the women empowerment, and a portrait of the changes in the local urban dynamic.